Analysis of Interactional And Transactional Language Used by The English Lecturers In Learning Process At English Department of FKIP UKI Toraja - Viktor Siumarlata (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
The objective of this research is to find out which is more dominant language used by the English lecturers in learning process at English Department of FKIP UKI Toraja interactional or transactional, and in what situation interactional and transactional language used by the English lecturers in learning process at English department of FKIP UKI Toraja. Descriptive qualitative and quantitative design is applied in this reserch to analyze the data. The data was analyzed was script from the result of recording video in learning process at English Department of FKIP UKI Toraja.The data was analized based on every utterance of lecturer in learning process. The writer used snow ball method in choosing sample of this research. The writer only took 5 lecturer as sample from the total population was 21 lecturers.From the data analysis, the writer found that transactional language more dominant used by the English lecturers in learning process. The result of this research shows that most of the lecturers used Transactional language in learning process then interactional. There are 1.194 utterances of transactional language used by the lecturers in learning process from the total number of utterances is 1.329. transactional language used in situation like greets student at begining of the class, explain topic, answer and giving question and when lecturer gives example for the students. After conducting this study, it is expected to give valuable contribution to the all lecturers in learning process and can be more variatif in using language. This research also is expected as additional knowledge and information for the all people specially to the students that interested in conducting similar study. The writer do hope as language user : reader, writer, and whoever that want to study more about interactional and transactional language can be more improved.